PERBANDINGAN PENDAPATAN USAHA TANI PADI MENURUT SISTEM MINA PADI DAN NON MINA PADI DI KECAMATAN PAKEM, KABUPATEN SLEMAN, D.I. YOGYAKARTA - Adimas Bayu Saputra (Fakultas Pertanian UST, 2017)
This study aimed to investigate the comparison of income and cost between minapadi culture system and non-minapadi culture system. The study was conducted in Desa Harjobinangun and Candibinangun, Kecamatan Pakem, Kabupaten Sleman on October-November 2015. The data sources were determined by random sampling and census sampling. The samples of this study consisted of 20 minapadi culture system and 30 non-minapadi culture system. Data were analyzed using analysis of cost, analysis of receipt and analysis of income whereas the hypothesis testing used t-Test. The result of the study showed that the revenue of minapadi culture system is (Rp 28 675 781,57)/ha, it is higher than non-minapadi culture system that is (14 790 229,90)/ha, and the t-Test showed that it is significant.Â Keywords: minapadi culture system, non-minapadi culture system